Biometric and intraocular pressure changes after Nd:YAG laser capsulotomy - Simsek, Ali (The European Research Journal, 2017)
Objective. We aimed to investigate the influences of Nd:YAG (neodymium-doped yttrium aluminum garnet) laser capsulotomy on ocular biometric parameters.Methods. In this prospective study, 117 eyes of 117 pseudophakic patients were included. Full ocular examination, the best-corrected visual acuity (BCVA), and intraocular pressure (IOP) measurements were performed before the procedure as well as one week, one month, and three months after Nd:YAG laser capsulotomy. The axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), and pupil diameter (PD) were measured by LenStar 900 optical biometry. The measurements were repeated one week, one month, and three months.Results. The BCVA improvements at preoperative, one week, and one month were statistically significant, but no significant changes in the BCVA were found at one month and three months (p=0.345). No association was found between the capsulotomy and mean IOP changes during the follow-up period (p=0.300). No significant changes were found in the CCT (p=0.059). The ACD changes occurred at preoperative; the first week and the first month were statistically significant (p